Pengertian, Konsep, Teori dan Lingkup Sistem dan Kebijakan Pendidikan Nasional - Fitri, Lidya; Fitrina Suanti; Ridwan Trisoni (Jurnal Dirosah Islamiyah, 2024)
The development of knowledge and technology greatly influences changes in educational goals every year. Education for humans is very important so the need for quality education is the main goal for creating human resources that are able to increase personal potential. The importance of national systems and policies cannot be underestimated. They have a direct impact on the quality of education received by the younger generation, social mobility, and the country's economic development. Therefore, the government and related stakeholders need to be actively involved in formulating effective policies, monitoring their implementation, and committing to continue improving the national education system for a bright future. This research aims to explain the meaning, concepts, theories and scope of the national education system and policies. The research method used is the library research method, which is a method that uses a library study approach by examining sources or references that are relevant to research problems to find answers to research problems. The research results show that it is important to develop a strong national education policy system to create an educated and competent society, which is ready to face the challenges of the times.